Pengaruh Suhu dan Waktu terhadap Yield dan Kemurnian Pupuk K2SO4 dari Abu Kulit Buah Kapuk dan Gipsum - Galu Murdikaningrum; kenny kencanawati (Sainteks: Jurnal Sain dan Teknik, 2020)
Indonesia is one of the largest agricultural countries in the world, with the majority of the population working as farmers. Theagricultural industry certainly needs fertilizer to maintain quality, accelerate growth and provide nutrients for plants to grow well. To provide cheap potassium sulphate fertilizer, we conducted a study on "The Effect of Temperature and Time on Yield andPurity K2SO4Fertilizer from gypsum and Ash Bark" as an alternative to commercially available ZK fertilizers. The reason we usedash bark was because it was a waste from cottonwood industry. This study used a single stage methodwhere in this method the final result was not recycled to save time.The variables used are temperature (60oC, 70oC, 80oC) and time (60, 90, 120 minutes). The results showed that the most K2SO4crystals were formed at 80oC for 120 minutes with potassium concentrations of 69.60%.Keywords: potassium sulphate fertilizer, single